Original paperDisease-induced level of shame in patients with acne, psoriasis and syphilis - Rzepa, Teresa; Jakubowicz, Oliwia; Witmanowski, Henryk; Żaba, Ryszard (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2013)
Introduction: A prolonged feeling of shame leads to particularly negative consequences and it accompanies, as well as triggers, any kind of stigma. Aim: As empirical works on shame due to stigmatizing diseases are scarce, the authors aimed to investigate the following: 1) which diseases are perceived as the most embarrassing, and 2) what level of shame is attributed to the embarrassing diseases by affected patients. Additionally, the authors assumed that the differentiation variable for the second aim would be the level of infectiousness (or non-infectiousness) of a given disease. Material and methods: A two-stage study was carried out in 2011–2013. Three groups of patients affected by various diseases were included into the actual study: 1) people suffering from non-infectious (42 psoriasis and 42 acne subjects) and 2) infectious (25 syphilis cases) diseases. The patients filled in an original questionnaire, designed especially for the purpose of the study. Results: As the most shameful acne patients consider syphilis, but patients with syphilis – AIDS. Patients with syphilis assigned to their disease the greatest shame (average 75%), and the lowest – acne patients (average 30%). Patients with psoriasis assessed on 52% shame experienced because of the disease. Conclusions : The conducted study confirmed the accuracy of the empirical assumptions which may be applicable in prevention as well as therapy of negative consequences of shame.